Strategi World Wide Fund for Nature (WWF) dalam Mendukung Program Blue Economy di Indonesia - Elfrinda Eka Febriana; Arie Kusuma Paksi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to explain the contribution of international organizations in preserving marine ecosystems in order to achieve sustainable economic development in Indonesia. The problem is focused on case studies of the World Wide Fund for Nature (WWF) on how WWF's strategy supports the program blue economy in Indonesia. The strategy includes policy advocacy, multi-stakeholder partnerships, sustainable marine resource management, local community development, and ecotourism promotion. In order to approach this problem, theoretical references from conceptual theory are used for Non-Governmental Organization (NGO). The data in this article were collected through a literature study method on (1) WWF and environmental programs in Indonesia, (2) Indonesia and its targets blue economy, and (3) WWF's strategy in Indonesia in supporting the program blue economy, and analyzed qualitatively. This study concludes that optimizing the program blue economy in Indonesia requires the role of various actors, such as the state, society, and even NGOs. Therefore, this study found that cooperation between actors can reap success in achieving targets blue economy in Indonesia.